CHANGES OF ENZ¥MATIC ACTIVITY DURING LARVAL DEVELOPMENT OF CARP, CATLA CATLA (HAM.) - CHAKRABARTI, RINA; SHARMA, JAI GOPAL (Journal of Indian Fisheries Association, 2015)
Quantitative assays of trypsin, amylase and alkaline phosphataseswere made in relation to age and food during the larval developmentof the Indian major carp Catla catla. The responses of all the testenzymes to age and food were identical. No enzymes were detected. from the fertilized eggs. Detectable amount of enzymes were firstobserved in the first day old hatchlings. All the test enzymes in thegroup fed normal feed tended to rise gradually with advancement ofage till day 22 after which an asymptotic level was attained. Absenceof food throughout the rearing period caused the enzymatic activity ofthe larva to remain at the lowest level throughout. When starvationwas followed by feeding, enzymatic activity in the former group wasconsistently higher than that of latter, suggesting that feeding activitywas primarily responsible in maintaining the enzymatic activity ofcarp larva. The enzymatic activit¥ of zooplankton was significantlyhigher than carp larva till d~y 6 ·to 12 after which the latter exceededthe former implying that carp larva during development utilizes theexogenous enzymes of zooplankton.